'Of Middle Eastern Appearance' is a Flawed Racial Profiling Descriptor. Issue 2 (1st November 2017) - Al-Natour, Ryan
Abstract: Arab Australian communities and social science academics have argued that the racial descriptor 'of Middle Eastern appearance' increases anti-Arab racism in Australia. These stakeholders argue this descriptor is heavily racialised, gendered, criminalised and inaccurately racially profiles Arabs as Muslims with a range of phenotypical characteristics. Identifying the flawed nature of this racial profiling descriptor, this article argues that this inaccuracy enables a range of discourses attempting to legitimise and undermine anti-Arab racism. The Cronulla pogrom of 2005 is examined as a case study that details these discourses. Ultimately, this article points out how this descriptor produces a number of paradoxes, limitations and unanswered questions common in attempts to racially profile Arab Australia.